Prevalence, risk factors and outcomes of neonatal hypothermia at admission at a tertiary neonatal unit, Kigali, Rwanda – a cross-sectional study. (2nd September 2021) - Urubuto, Fedine; Agaba, Faustine; Choi, Jaesok; Dusabimana, Raban; Teteli, Raissa; Kumwami, Muzungu; Conard, Craig; O'Callahan, Cliff; Cartledge, Peter
Abstract: Introduction: Thermoregulation remains a key physiological challenge faced by a neonate after delivery. We assessed the prevalence, risk factors and outcomes of hypothermia in admitted neonates at a tertiary teaching hospital of Kigali city in Rwanda. Materials and methods: A cross-sectional study was conducted, from July 2013 to September 2017, of neonates who were admitted in the neonatology unit of the University Teaching Hospital of Kigali (CHUK) and whose admission temperature were recorded. Data were extracted from the neonatal database (registry). Results: The neonatal database contained 1021 eligible neonates of which 15% were outborn. Hypothermia was found at admission in 280 of the 1021 eligible neonates (27%). The extremely preterm (<28 weeks) were significantly more likely to become hypothermic compared to term neonates (AOR = 6.81, CI: 3.39–13.71, p < .001). Mortality rate was higher in hypothermic infants (AOR = 1.89, CI: 1.16–3.1, p = .011). Length of hospital stay (22 versus 13 days, p < .001), in all surviving infants was higher in neonates admitted hypothermic, though not in the subgroups of infants < 32-week gestation. Discussion: Thermal protection of the neonate immediately after birth is essential. In our tertiary neonatal unit, we identify nearly one-third of neonates are hypothermic at admission and this is associated with higher mortality and increased length of hospital stay. The ten-steps of the WHO "warm chain" may present an analytic roster for maternity and neonatal teams to pinpoint targets for interventional research and quality improvement work in order to achieve better outcomes.